Pendampingan Pembelajaran Ilmu Tajwid Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Di TPQ Nurul Huda Dusun Pusuh Besowo Timur Kecamatan Kepung Kediri - Doni Saputra; Izza Masrukhatur Rodhiyah; Mawaddatur Rohmah (LP3M IAIFA Kediri, 2023)
From an early age, in the landfill and school we have been introduced and taught various hijaiyah letters and accompanied by learning tajwid science, so that after adolescence we are able to read the Qur'an properly and correctly. But in fact there are still many children who have memorized the hijaiyah letters but are still not correct in reading the Qur'an because they do not understand the science of Tajwid, therefore, we provide assistance in learning tajwid science to TPA students so that they can understand tajwid science and can apply it in reading the Qur'an. In this study the authors chose the PAR method. The results of this study are obtained with the following steps: The first step we do is to prepare the material that we will deliver. The second step is to implement a learning assistance plan. The third step is to evaluate the learning assistance that has been carried out.